Determinant of non-audit services : evidence from Malaysian listed companies / Jessieca Cherryl Yatan - Yatan, Jessieca Cherryl (2015)
This paper aims to investigate the relationships between independent variables and non-audit service provision in the context of Malaysian Listed Companies. The sample consists of 709 listed companies in Bursa Malaysia that are identified in 2014 financial year. The companies are from eleven industries, which are construction, consumer product, finance, hotels, industrial product, infrastructure project company, plantation, properties, REITS, trading and services and technology There are six independent variables that being tested in this study, which are CEO duality, board independence, type of auditor and audit committee's characteristics that only focus on size, independence and meetings. Company size, profitability, leverage, growth and industry are being include act as the control variables. The theoritical framework indicates that these six variables will influence the purchased of nonaudit services. Using the logistic regression model and relevant diagnostic tests, findings shows that only board independence, audit committee's independence, type of auditor, profit, hotel industry and REITS industry are associated with the level of purchased non-audit services. This study provides unique contribution of the determinant of purchased non-audit services. It concludes that others corporate governance factors should also be tested in order to have more accurate and useful data in determine the level of purchased non-audit services in Malaysia.